Online assessment of narrative macrostructure in adult Irish-English multilinguals - Antonijevic, Stanislava; Colleran, Sarah; Kerr, Clodagh; Ní Mhíocháin, Treasa (Frontiers in Psychology, 2022)
Background Online assessment of narrative production and comprehension became an important component of language assessment during the COVID-19 pandemic. This study aimed to establish quantitative measures of narrative macrostructure in the production and comprehension of adult Irish-English bilinguals in an online assessment. Methods A total of 30 Irish-English bilingual adults participated in an online assessment of oral narrative production and comprehension. Narratives were elicited using LITMUS-MAIN for Irish and English. Story-tell elicitation method was used for all stories. Twenty participants produced Baby Birds and Baby Goats story pairs while 10 participants produced Cat and Dog story pairs. Quantitative measures of story structure, comprehension score, and the overall number of Internal State Terms (ISTs) in production and comprehension were compared across the story pairs, languages, and the output type (production vs. comprehension). Results A general linear model indicated no differences in either story structure or story comprehension scores across languages for both sets of stories. Combined analysis for all participants and stories indicated no difference in the story structure scores or comprehension scores across the languages or the story pairs. While the overall number of ISTs was the same across languages, a higher number of ISTs was observed in comprehension relative to production in both languages for Cat and Dog story pair only, but not for Baby birds and Baby goats' stories. The major benefit of using online assessment was the accessibility of participants. The major drawback was the inability to control the environment and the quality of the internet connection. Conclusion and implications While online assessment increased the availability of participants, which is a significant factor in rural Ireland characterized by low population density and the high percentage of Irish speakers, the availability of stable internet connection limited the applicability of online assessment. Measures of narrative macrostructure were stable across the languages and the story pairs. This is important because of high variability in exposure to Irish, frequent code-switching, and a high number of morphosyntactic errors due to rapid language change that characterizes Irish-English bilinguals. Identifying reliable measures of language performance for Irish-English adult speakers is an important step toward establishing developmental norms for Irish-English bilinguals.